Optimization of EDM Process Parameters on Machining Characteristics of SiC and Graphene Reinforced Al 6061-T6nano-Composites. Issue 1 (April 2021) - Ammisetty, Saikiran; Ammisetti, Dhanunjaykumar; Satyanarayana, K.; Chitturi, Suresh; Naik, N.Sunil
Abstract: Aluminum composites play an important role in various applications due to their low weight to strength ratio, high corrosive resistance, etc. As reinforcement materials, Graphene and SiCnano particles were used. Since, they havea high melting point, young modules, strong electrical and thermal properties etc. Electrical Discharge Machining (EDM) is one of the non-conventional machining techniques widely used for the machining of hard materials such as composites. The aim of current work is to evaluate the influence of EDM process parameters such as peak current, pulse on-time, voltage and flushing pressure on machining of Aluminium 6061 reinforced with 0.5 wt% SiC and 0.5 wt% Graphene nanoparticles. Al-based Metal Matrix Composite was casted by using liquid processing technique i.e. Stir Casting. Taguchi's Design of Experiments was used to evaluate the effect of process parameters on machining characteristics i.e. Material Removal Rate (MRR) and Tool Wear Rate (TWR) of developed composite. From the results it was observed that peak current is the most influencing factor on MRR and TWR followed by other parameters.